2017
DOI: 10.1101/197269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PeatlandAcidobacteriawith a dissimilatory sulfur metabolism

Abstract: Sulfur-cycling microorganisms impact organic matter decomposition in wetlands and consequently greenhouse gas emissions from these globally relevant environments. However, their identities and physiological properties are largely unknown. By applying a functional metagenomics approach to an acidic peatland, we recovered draft genomes of seven novel Acidobacteria species with the potential for dissimilatory sulfite (dsrAB, dsrC, dsrD, dsrN, dsrT, dsrMKJOP) or sulfate respiration (sat, aprBA, qmoABC plus dsr … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…The N. marina genome also contains an alternative complex III (ACIII) module, which shares similarity with that from sulfur-reducing Acidobacteria [58]. (Table S5).…”
Section: Genome Analysismentioning
confidence: 99%
“…The N. marina genome also contains an alternative complex III (ACIII) module, which shares similarity with that from sulfur-reducing Acidobacteria [58]. (Table S5).…”
Section: Genome Analysismentioning
confidence: 99%
“…Many of these functional traits are evolutionarily selected for in response to environmental conditions. In general, metagenomic studies of peatlands have been concentrated in the northern hemisphere, but have provided valuable insights into key functions and microbial populations involved in the biogeochemical cycles occurring in northern peat soils [17,23,25]. Metagenomic studies in tropical peatlands are rare and, to our knowledge, there is no published metagenomic study for peatlands found in the Amazon.…”
Section: Introductionmentioning
confidence: 99%